Analisis Kinerja Reksa Dana Saham Syariah Sebelum Dan Setelah Penerapan Roadmap Pasar Modal Syariah 2020-2024 - Apriyadi, Pidi; Cupian, Cupian (Jurnal Ilmiah Ekonomi Islam, 2024)
The Islamic capital market in Indonesia has witnessed significant progress, particularly in the development of products such as Shariah equity mutual funds. In the period 2017-2022, the Net Asset Value (NAV) of Shariah equity mutual funds reached IDR 153,40 trillion. However, in terms of performance, Shariah equity mutual funds still recorded minor results. The Financial Services Authority (OJK) has endeavored to enhance the potential of the Islamic capital market through the launch of the Shariah Capital Market Roadmap 2020-2024. To evaluate the positive impact of this policy, this research examines the factors influencing the performance of Shariah equity mutual funds during the period 2017-2022. A quantitative descriptive approach is employed using non-probability judgement sampling. Panel data is analyzed using multiple linear regression, with dummy variables used to identify performance differences before and after the implementation of the Shariah Capital Market Roadmap 2020-2024. Research findings indicate that cashflow, IHSG (Indonesia Stock Exchange Composite Index), and the age of Shariah equity mutual funds significantly influence performance. However, the impact of NAV is observed but not statistically significant. The dummy variable shows a negative and significant value, indicating performance differences between the two observed periods